2015
DOI: 10.6001/actamedica.v21i4.3045
|View full text |Cite
|
Sign up to set email alerts
|

Preterm premature rupture of membranes at 32–34 weeks of gestation: duration of membrane rupture period and maternal blood indicators relation with congenital infection

Abstract: Background. The study investigates the influence of the length of membrane rupture period among pregnant women with preterm premature rupture of membranes (PPROM) between the 32nd and 34th weeks of gestation on the development of chorioamnionitis and the congenital infection of a newborn. It seeks to ascertain the values of indicators in mother's blood that enable to predict chorioamnionitis and funisitis for mothers, and congenital infection for newborns.Materials and methods. A retrospective study of case re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…In contrast, other studies did not prove any significant predictive value of the WBC count. [31,32] The current study showed the same results. In contrast, some studies have shown different results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast, other studies did not prove any significant predictive value of the WBC count. [31,32] The current study showed the same results. In contrast, some studies have shown different results.…”
Section: Discussionsupporting
confidence: 81%
“…As the more extended leaking period of the membrane rupture is correlated with histological chorioamnionitis, funisitis and congenital infection. [32] Other studies reported that the prolonged duration of the membrane rupture period had a significant factor for chorioamnionitis. [36,37] It is clear that the current study has the same result as the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sample Size: To compute for the sample size, we calculated for the minimum sample required for both HCA and for EONS and the higher sample size was followed in this study. The values used for this sample size computation was based on a study by Daunoravičienė et al in 2014 12 . The calculations are presented below.…”
Section: Ementioning
confidence: 99%
“…This value gives 80% power to detect an effect size of 15.7 at 0.05 α-level of significance. The values used for this sample size computation were based on a study by Daunoravičienė et al 2014 12 .…”
Section: Ementioning
confidence: 99%
“…El contaje de leucocitos mayor de 15.000 por milímetro cúbico, se ha asociado con la presencia de infección corioamniótica; sin embargo, este hallazgo puede resultar poco confiable, puesto que, puede existir leucocitosis en casos de administración antenatal de corticosteroides y en presencia de trabajo de parto lo que complica más aún el diagnóstico (Daunoraviciene, 2014).…”
Section: Introductionunclassified